2021
DOI: 10.1029/2020ja028675
|View full text |Cite
|
Sign up to set email alerts
|

Statistically Determining the Spatial Extent of Relativistic Electron Precipitation Events Using 2‐s Polar‐Orbiting Satellite Data

Abstract: Within Earth's magnetosphere lie the Van Allen radiation belts, surrounding the Earth with energetic, charged particles. Under typical geomagnetic conditions, there are two such belts-a relatively stable inner belt, and a dynamic outer belt composed of electrons and low-energy protons, typically confined within 3 ≤ L ≤ 8 (e.g., Millan & Baker, 2012;Millan & Thorne, 2007). Outer belt electrons with relativistic energies often remain trapped by Earth's magnetic field for less than a day before either escaping ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 33 publications
(94 reference statements)
6
13
0
Order By: Relevance
“…Similar to previous studies (e.g., Gasque et al., 2021), the observed wave‐driven REP occurs on small radial scales, typically <0.3 L , likely because the regions where wave‐particle interactions drive efficient pitch angle scattering are just as localized. Additionally, we also showed that pre‐midnight wave‐driven REP events tend to exhibit a maximum radial spatial scale of ∼0.7 L , while the ones detected in the post‐midnight sector are typically <∼0.5 L .…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Similar to previous studies (e.g., Gasque et al., 2021), the observed wave‐driven REP occurs on small radial scales, typically <0.3 L , likely because the regions where wave‐particle interactions drive efficient pitch angle scattering are just as localized. Additionally, we also showed that pre‐midnight wave‐driven REP events tend to exhibit a maximum radial spatial scale of ∼0.7 L , while the ones detected in the post‐midnight sector are typically <∼0.5 L .…”
Section: Discussionsupporting
confidence: 87%
“…Similar to previous studies (e.g., Gasque et al, 2021), the observed wave-driven REP occurs on small radial scales, typically <0.3 L, likely because the regions where wave-particle interactions drive efficient pitch angle scattering are just as localized. Additionally, we also showed that pre-midnight wave-driven REP events tend to exhibit a maximum radial spatial scale of ∼0.7 L, while the ones detected in the post-midnight sector are typically <∼0.5 L. This is an interesting result that requires further understanding of the wave properties and wave-electron interactions that could justify why the precipitation extent seems to be asymmetric with respect to midnight.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations